Rice transformation with cell wall degrading enzyme genes from Trichoderma atroviride and its effect on plant growth and resistance to fungal pathogens - Liu Mei; Sun Zong-Xiu; Zhu Jie; Xu Tong; Gary E Harman; Matteo Lorito; Sheri Woo (浙江大学学报. 农业与生命科学版)
Three genes encoding for fungal cell wall degrading enzymes (CWDE), ech42, nag70 and gluc78 from the biocontrol fungus Trichoderma atroviride were inserted into the binary vector pCAMBIA1305.2 singly and in all possible combinations. The coding sequences were placed downstream of the rice actin promoter and all vectors were used to transform rice plants. A total of more than 1, 800 independently regenerated plantlets in seven different populations (for each of the three genes and each of the four gene combinations) were obtained. Expression in plant was obtained for all the fungal genes used singly or in combinations. The ech42 gene encoding for an endochitinase increased resistance to sheath blight caused by Rhizoctonia solani, while the exochitinase-encoding gene, nag70, had a lesser effect. The expression level of endochitinase but not of the exochitinase was correlated with disease resistance. Nevertheless, exochitinase enhanced the positive effect of endochitinase on disease resistance when two genes were co-expressed in transgenic rice. Improved resistance to Magnaporthe grisea was found in all types of regenerated plants, including those with the gluc78 gene alone, while a few lines expressing either ech42 or nag70 appeared to be immune to this pathogen. Transgenic plants expressing the gluc78 gene alone were stunted and only few of them survived, even though they showed resistance to M. grisea. However, combination with either one of the two other genes (ech42, nag70) as included in the same T-DNA region, reduced the negative effect of gluc78 on plant growth. This is the first report of single or multiple of expression of transgens encoding CWDEs that results in resistance to blast and sheath blight in rice.